INTERNALISASI PENDIDIKAN KARAKTER DI SEKOLAH - Arfandi Arfandi; Munif Shaleh (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2016)
Integrating character education in learning involvesome points. As we know that recognition pointis the essence of education that is the recognition of the human dignity of every individual human being. Furtherconsciousness point is important that teacher to be a good educator who is loved by students, and then internalization point that intended to studentâ€™s behavior by teaching everyday in the learning process at school, mainly by teaching directly in the class on all of subject lessons. It has been mandated by UU SISDIKNAS 2003 that education is not only toforming the intelligent ofpeoples in Indonesia, but also got thepersonality or character.Education that has a purpose to forming smartand strong character peoples has been in resolution by Martin Luther King,â€intelligence plus character, that is goal of true education â€.